EVALUASI PROGRAM PENDAMPINGAN PENGEMBANGAN KEPRIBADIAN MUSLIM INTEGRAL (P3KMI) DI JURUSAN PENDIDIKAN GURU RAUDHATUL ATHFAL FAKULTAS ILMU TARBIYAH DAN KEGURUAN IAIN SURAKARTA TAHUN 2016 - Junanto, Subar (Jurnal Penelitian, 2016)
AbstractProblems in the study faced by Program Pendampingan Pengembangan Kepribadian Muslim Integral (P3KMI), which is the implementation of learning that sometimes does not correspond to the learning schedule that includes the implementation time and duration, in addition to the program material is sometimes not in accordance with the target implementation P3KMI. So it is necessary to evaluate for Program Pendampingan Pengembangan Kepribadian Muslim Integral (P3KMI). The purpose of this study was to evaluate Program Pendampingan Pengembangan Kepribadian Muslim Integral (P3KMI) in Raudhatul Athfal Departement At Tarbiyah And Teacher Training Faculty  IAIN Surakarta in 2016 using CIPP MODEL.This study uses a mix method, which incorporates quantitative and qualitative research. This research was conducted in evaluating Program Pendampingan Pengembangan Kepribadian Muslim Integral (P3KMI). Raudhatul Athfal Departement At Tarbiyah And Teacher Training Faculty  IAIN Surakarta in 2016. mentee and mentor of P3KMI. Data collection techniques using observation, interviews, documentation and questionnaire. The focus of the evaluation in the form of context, input, process and product of P3KMI. Data were analyzed using qualitative analysis and statistical analysis.